Cognitive and Operational Implications of Non-Homogeneous - Pina, Patricia; Hansman, R. John (2007)
The air traffic management system is currently experiencing a significant transformation to provide better quality service and to match the increasing air traffic demand. This transformation requires airlines to retrofit their fleet. However, airlines implement new operating capabilities at different rates resulting in long transition periods in which aircraft with different equipage levels coexist in the same airspace. Mixed equipage environments can increase controller workload and task complexity, limit the operational benefits of new operating capabilities, and deteriorate the overall system performance. This study proposes a three dimensional approach to explore mixed equipage effects: (1) understand cognitive implications for controllers, (2) understand operational implications for users, and (3) understand system level implications. To further investigate mixed equipage effects and to illustrate the proposed approach, this study analyzed the implementation of reduced separation standards in the North Atlantic.